1997
DOI: 10.1074/jbc.272.39.24612
|View full text |Cite
|
Sign up to set email alerts
|

Expression Cloning of a Rat Hypothalamic Galanin Receptor Coupled to Phosphoinositide Turnover

Abstract: The neuropeptide galanin is widely distributed throughout the central and peripheral nervous systems and participates in the regulation of processes such as nociception, cognition, feeding behavior, and insulin secretion. Multiple galanin receptors are predicted to underlie its physiological effects. We now report the isolation by expression cloning of a rat galanin receptor cDNA distinct from GALR1. The receptor, termed GALR2, was isolated from a rat hypothalamus cDNA library using a 125 I-porcine galanin (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
200
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(211 citation statements)
references
References 37 publications
10
200
1
Order By: Relevance
“…Among these receptors, GalR1 and GalR3 mainly activate G i/o types of G proteins mediating inhibitory actions of galanin (Habert-Ortoli et al, 1994;Burgevin et al, 1995;Parker et al, 1995;see Branchek et al, 2000). In contrast, the GalR2 subtype can transmit either stimulatory effects of galanin, for example, on neurotransmitter release, acting via G q/11 types of G proteins (Smith et al, 1997;Wang et al, 1997;Fathi et al, 1998), or it can inhibit neurotransmission via G i/o types (Fathi et al, 1998;Wang et al, 1998;see Branchek et al, 2000). Thus, the physiological effects of galanin are varied and complex.…”
Section: Introductionmentioning
confidence: 99%
“…Among these receptors, GalR1 and GalR3 mainly activate G i/o types of G proteins mediating inhibitory actions of galanin (Habert-Ortoli et al, 1994;Burgevin et al, 1995;Parker et al, 1995;see Branchek et al, 2000). In contrast, the GalR2 subtype can transmit either stimulatory effects of galanin, for example, on neurotransmitter release, acting via G q/11 types of G proteins (Smith et al, 1997;Wang et al, 1997;Fathi et al, 1998), or it can inhibit neurotransmission via G i/o types (Fathi et al, 1998;Wang et al, 1998;see Branchek et al, 2000). Thus, the physiological effects of galanin are varied and complex.…”
Section: Introductionmentioning
confidence: 99%
“…Three subtypes of galanin receptors have been cloned, GalR1 (Habert-Ortoli et al 1994;Burgevin et al 1995;Parker et al 1995) GalR2 (Howard et al 1997;Smith et al 1997;Wang et al 1997a) and GalR3 (Wang et al 1997b;Smith et al 1998), which all belong to the superfamily of G-protein-linked receptors. The autoradiographic receptor binding studies have indicated moderate galanin R1 and R2 receptor binding in the DRN .…”
Section: Discussionmentioning
confidence: 99%
“…GALR2 is more widely distributed in peripheral tissues and to a lesser extent in the central nervous system (Wang and Gustafson, 1998). Most authors describe the receptor's ability to activate phospholipase C-b in a pertussis toxin-insensitive manner, representing indirect evidence for coupling to G q proteins (Pang et al, 1998;Smith et al, 1997;. GALR3 is prominently expressed in spleen, heart and testis as well as in several regions of Figure 7 Stimulation of GALR2 causes the reorganization of the actin cytoskeleton in Swiss 3T3 ®broblasts.…”
Section: Discussionmentioning
confidence: 99%
“…While most authors agree on the receptor's ability to couple to phospholipase C-b isoforms via G q/11 proteins, the additional interaction of GALR2 with G i or G o is discussed controversially (Pang et al, 1998;Smith et al, 1997;Wang et al, 1997a. The galanin-induced inhibition of isoproterenoldependent cAMP accumulation in HEK293 cells coexpressing the human b 2 AR and GALR2 is considerably smaller than the e ect of carbachol acting on the M 2 muscarinic receptor.…”
Section: Discussionmentioning
confidence: 99%